Gambaran tentang Kegiatan Penyuluhan Kesehatan Menurut Lansia di Posyandu Sungai Asam Kabupaten Padang Pariaman - Hermanto, Deri; Sunarti, Vevi (Penerbit Aksara Rentaka Siar (ARS), 2019)
Background of this research of the elderly in the Sungai Asam Posyandu in Kabupaten Padang Pariaman. The purpose of this study is to describe the knowledge of lansi, the attitude of the elderly. This descriptive quantitative, the population to 30 people. Samples were taken as much as 65%. The number of samples is 20 people. The sampling technique uses simple random sampling. Data collection techniques used were questionnaires, while the data collection tools used questionnaires. The data analysis technique uses the percentage formula knowledge of the elderly to participate in health education was categorized as sufficient, the attitude of the elderly to follow health education was categorized as sufficient, and learning independence to take part in training activities was categorized as high.